Hubungan Tingkat Aktivitas Fisik Dengan Derajat Hipertensi Pada Lansia - Zuriati Zuriati; Siti Mis Mishataul; melti Suriya (Jurnal Kesehatan Bhakti Husada, 2026)
Background: Hypertension is one of the most prevalent chronic diseases among older adults and a major contributor to cardiovascular morbidity and mortality. Physical activity is a modifiable factor that plays an important role in blood pressure control. This study aimed to examine the association between physical activity level and hypertension severity among older adults. Methods: A quantitative cross-sectional study was conducted among 60 older adults diagnosed with hypertension using an accidental sampling technique. Physical activity was assessed using the Physical Activity Scale for the Elderly (PASE), while hypertension severity was determined from blood pressure measurements. Data were analyzed using descriptive statistics and the Chi-square test. Results: Among the participants, 31 (51.7%) had low physical activity levels, and 24 (40.0%) were classified as having Grade 2 hypertension. Chi-square analysis revealed a statistically significant association between physical activity level and hypertension severity (p < 0.001). Older adults with low physical activity were more likely to experience more severe hypertension than those with moderate or high physical activity levels. Conclusion: Physical activity level was significantly associated with hypertension severity among older adults. Promoting regular physical activity through community-based hypertension management programs, including routine exercise at Integrated Non-Communicable Disease Service Posts may improve blood pressure control and reduce the risk of cardiovascular complications